Overweight and obesity among mothers of malnourished children - Brazil - PNSN - 1989 - Rodrigues, Eliana Monteiro; Taddei, José Augusto de Aguiar Carrazedo; Sigulem, Dirce Maria (São Paulo Medical Journal, 1998)
OBJECTIVE: To evaluate the relationship between the nutritional status of the youngest child under 48 months of age (in families with the biological mother present) and their mothers among 3906 children selected from a sample of a national survey in 1989 (PNSN). RESULTS: Malnutrition was present in 5.8% of the children. From these, 21.8%, 60.9% and 17.3% had overweight/obese, eutrophic and malnourished mothers, respectively. Stratified analyses taking into account the regions, situation, income distribution and mother’s educational level demonstrated that a lower proportion of malnourished children was concurrent with a higher proportion of overweight/obese mothers. The Kappa test evidenced a poor agreement between the nutritional conditions of the child-mother pairs (K<=0.048). CONCLUSIONS: When the proportion of malnourished children decreased within the analyzed groups, the proportion of overweight/obese mothers increased. Such an epidemiological pattern indicates that within groups in which malnutrition is less prevalent, the proportion of children for whom a lack of food in the household is the main determinant factor for malnutrition is lower.